2009
DOI: 10.1007/s10551-009-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Food Advertising Targeted Toward Children: Parental Viewpoint

Abstract: parents, children, ethics, food advertising,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 27 publications
1
32
0
2
Order By: Relevance
“…Prior research on parental attitudes of children's advertising has revealed links between one's parenting style and parental perceptions of the advertising in question (Bakir and Vitell 2010;Carlson, Laczniak, and Muehling 1994;Crosby and Grossbart 1984;Grossbart and Crosby 1984). Authoritarian and authoritative parents typically hold more negative attitudes toward children's toy-based programming and food-based advertising compared to both indulgent and neglecting parents (Carlson, Laczniak, and Muehling 1994;Crosby and Grossbart 1984;Grossbart and Crosby 1984).…”
Section: Parents' Attitudes Toward Advertisingmentioning
confidence: 99%
“…Prior research on parental attitudes of children's advertising has revealed links between one's parenting style and parental perceptions of the advertising in question (Bakir and Vitell 2010;Carlson, Laczniak, and Muehling 1994;Crosby and Grossbart 1984;Grossbart and Crosby 1984). Authoritarian and authoritative parents typically hold more negative attitudes toward children's toy-based programming and food-based advertising compared to both indulgent and neglecting parents (Carlson, Laczniak, and Muehling 1994;Crosby and Grossbart 1984;Grossbart and Crosby 1984).…”
Section: Parents' Attitudes Toward Advertisingmentioning
confidence: 99%
“…Despite the importance of parents in influencing ethical considerations of children (Bakir and Vitell 2010), we know little about how much they can influence ethical attitudes towards questionable online activities. Nor do we know how strong peer influence is in comparison to parenting style in determining online ethical attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to food advertisements affects food choices among children (e.g., Halford, Boyland, Hughes, Oliveira, & Dovey, 2007). Researchers have been discussing various ethical issues of food advertising on children (e.g., promotion of unhealthy food; Bakir & Vitell, 2010). To reduce the negative effect of advertisements on consumers' well-being, Kramer (2006) suggests that social marketers create counteradvertisements and discourage materialism.…”
Section: Limitations and Future Researchmentioning
confidence: 99%